Value And Self-Concept : A Study On Reading Habits Among Primary School Students In Sarawak - Ambigapathy, Pandian; Keezrawati, Mujan Yusuf; Dexter Sigan, John (AESS Publications, 2019)
This study analyses the extent to which students‟ value of reading and self-concepts as readers affect their motivation to read. The participants included 45 students from a rural primary school in Malaysia aged 8 to 10 years old. They completed the Motivation to Read Profile-Revised (MRP-R) designed by Malloy et al. (2013) which consists of a survey and conversational interview to shed light on students‟ attitudes towards reading. The results from the survey demonstrated that the students held high self-concepts of themselves as readers and were able to use reading comprehension strategies. Overall they found reading enjoyable, and preferred collaborative reading tasks and books with visuals. Additionally, students were motivated by engaging classroom activities and trips to the library, and many students preferred digital text. However, the students found reading in another language to be challenging. Through these results, the role of the teacher is highlighted as essential in motivating students to read. By providing opportunities for students to read a variety of texts at students‟ reading levels and on different topics, in both students‟ native languages and target language. Students may gain reading motivation when they can choose what to read and when instructors create engaging activities that encourage not only independent reading, but incorporate a social aspect as well. Schools may also consider using technology to motivate young readers, and a reading culture should be supported in the students‟ homes to further encourage lifelong reading habits.